2020
DOI: 10.1002/ana.25734
|View full text |Cite
|
Sign up to set email alerts
|

Left Prefrontal Connectivity Links Subthalamic Stimulation with Depressive Symptoms

Abstract: Objective: Subthalamic nucleus deep brain stimulation (STN-DBS) in Parkinson's disease (PD) not only stimulates focal target structures but also affects distributed brain networks. The impact this network modulation has on non-motor DBS effects is not well-characterized. By focusing on the affective domain, we systematically investigate the impact of electrode placement and associated structural connectivity on changes in depressive symptoms following STN-DBS, which have been reported to improve, worsen, or re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 57 publications
4
61
1
Order By: Relevance
“…Hence, we proposed that STN-DBS before L-Dopa therapy could further promote a longer-lasting physiological and psychosocial functioning and positively modulate the neurodegenerative process. This hypothesis finds support on recent reports on the potential of DBS to shift the network response toward the physiological range (Kim et al, 2015;Horn et al, 2019), whereas DBS outcomes have been constantly related to the integrity of widespread brain regions connected to the stimulation sites in PD (Muthuraman et al, 2017;Koirala et al, 2018;Irmen et al, 2020) and in other diseases (Gonzalez-Escamilla et al, 2019). Thus, an effect on the neurodegenerative side is also expected.…”
Section: Discussionsupporting
confidence: 83%
“…Hence, we proposed that STN-DBS before L-Dopa therapy could further promote a longer-lasting physiological and psychosocial functioning and positively modulate the neurodegenerative process. This hypothesis finds support on recent reports on the potential of DBS to shift the network response toward the physiological range (Kim et al, 2015;Horn et al, 2019), whereas DBS outcomes have been constantly related to the integrity of widespread brain regions connected to the stimulation sites in PD (Muthuraman et al, 2017;Koirala et al, 2018;Irmen et al, 2020) and in other diseases (Gonzalez-Escamilla et al, 2019). Thus, an effect on the neurodegenerative side is also expected.…”
Section: Discussionsupporting
confidence: 83%
“…As mentioned above, studies have begun to investigate the relationship between clinical improvement following DBS and connectivity between the active stimulation site and the rest of the brain ( Akram et al, 2018 ; 2017 ; Al-Fatly et al, 2019 ; Baldermann et al, 2019b ; Calabrese et al, 2015b ; Fernandes et al, 2015 ; Horn et al, 2017 ; Irmen et al, 2019 ; Joutsa et al, 2018a ; Li et al, 2020 ; Vanegas Arroyave et al, 2016 ).…”
Section: Eight Opportunities Of Connectomic Neuromodulationmentioning
confidence: 99%
“…Irmen et al demonstrated that in each of three PD cohorts undergoing STN-DBS at different centers, structural connectivity between DBS electrodes and the left prefrontal cortex was associated with the occurrence of depressive symptoms after surgery ( Irmen et al, 2019 ). The finding was highly reproducible and allowed robust cross-predictions across cohorts.…”
Section: Eight Opportunities Of Connectomic Neuromodulationmentioning
confidence: 99%
“…Even if it is current spread to STN subterritories and adjacent structures, and not modulation of the motor STN per se that drives reward-seeking deficits, this still does not explain the precise mechanisms underlying these deficits. For example, the reward-related effects could also be due to antidromic activation of afferent structures such as the prefrontal cortex (Irmen et al, 2020), or to modulation of downstream structures such as ventral pallidum or nucleus accumbens (Hahn et al, 2008;Cavdar et al, 2018). Likewise, STN-DBS modulates dopamine tone through polysynaptic outputs of the STN proper leading to stimulation of midbrain dopamine neurons, or through direct activation of dopamine fibers arising from current spread beyond the STN borders (Benazzouz et al, 2000a;Bruet et al, 2001;Tan et al, 2011Tan et al, , 2012Carcenac et al, 2015).…”
Section: Stn-dbs Potentially Induces Ectopic Stimulationmentioning
confidence: 99%